Answer:
[tex]f(a) = 4a - 1[/tex]
[tex]f(a+h) = 4a+4h - 1[/tex]
[tex]f(a + h) - f(a)h= 4a + 5h - 4ah- 1[/tex]
Step-by-step explanation:
Given
[tex]f(x) = 4x - 1[/tex]
Solving (a): f(a)
Substitute a for x
[tex]f(a) = 4a - 1[/tex]
Solving (b): f(a + h)
Substitute a + h for x
[tex]f(a+h) = 4(a+h) - 1[/tex]
[tex]f(a+h) = 4a+4h - 1[/tex]
Solving (c):f(a + h) - f(a)h
[tex]f(a + h) - f(a)h= f(a + h) - f(a) * h[/tex]
Substitute values for f(a + h) and f(a)
[tex]f(a + h) - f(a)h= 4a + 4h - 1 - (4a- 1) * h[/tex]
Open bracket
[tex]f(a + h) - f(a)h= 4a + 4h - 1 - 4ah+ h[/tex]
Collect like terms
[tex]f(a + h) - f(a)h= 4a + 4h + h - 4ah- 1[/tex]
[tex]f(a + h) - f(a)h= 4a + 5h - 4ah- 1[/tex]